Boundaries of Geoheritage in the Tafilalt and Maïder Regions, an Eldorado for Palaeozoic Cephalopods - Christian Klug; Carole Naglik; Merle Greif; Amin El Fassi El Fehri; Kenneth De Baets; Dieter Korn; Wahiba Bel Haouz; Abdelouahed Lagnaoui; Alexander Pohle (Geoheritage, 2026)
Morocco is world-renowned for its spectacular fossil record, spanning (among others) long intervals of the Palaeozoic. While large vertebrates or spectacular geological features and landscapes usually receive the most attention, we discuss the extraordinarily diverse and abundant cephalopod occurrences in the eastern Anti-Atlas and their role as geoheritage. We describe five remarkable geosites with their regional context including landscapes, touristic highlights and spectacular geomorphological structures. We use a standardised approach to assess the quality of these geosites according to their scientific, educational and touristic value. Additionally, we discuss potential strategies to manage geoheritage in the eastern Anti-Atlas, considering possible sites to be developed or protected, as well as geopolitical conflicts. We also provide some information about the new legal context. Finally, we shortly discuss whether protective measures are required. Clinical trial number: not applicable.